Impact of comorbidities and delay in diagnosis in elderly patients with pulmonary hypertension. Issue 4 (28th November 2018) - Ginoux, Marylise; Turquier, Ségolène; Chebib, Nader; Glerant, Jean-Charles; Traclet, Julie; Philit, François; Sénéchal, Agathe; Mornex, Jean-François; Cottin, Vincent
Patient age at diagnosis of pulmonary hypertension is steadily increasing. The present study sought to analyse clinical characteristics, time to diagnosis and prognosis of pulmonary hypertension in elderly and very elderly patients. A study was conducted in a French regional referral centre for pulmonary hypertension. All consecutive patients diagnosed with pre-capillary pulmonary hypertension were included and categorised according to age: <65 years ("young"), 65–74 years ("elderly") and ≥75 years ("very elderly"). Over a 4-year period, 248 patients were included: 101 (40.7%) were young, 82 (33.1%) were elderly and 65 (26.2%) were very elderly. The median age at diagnosis among the total population was 68 years. Compared with young patients, elderly and very elderly patients had a longer time to diagnosis (7±48, 9±21 and 16±32 months, respectively; p<0.001). Patients ≥75 years also more often had group 4 pulmonary hypertension. The median overall survival was 46±1.4 months, but was only 37±4.9 months in elderly patients and 28±4.7 months in very elderly patients. Survival from the first symptoms and survival adjusted to comorbidity was similar across age groups. Patient age should be taken into account when diagnosing pulmonary hypertension as it is associated with a specific clinical profile and a worse prognosis. The difference in prognosis is likely to be related to a delay in diagnosis and a greater number of comorbidities. More than a quarter of patients diagnosed with pre-capillary pulmonary hypertension are older than 75 years; they have a poorer prognosis, likely related to a longer delay in diagnosis and a higher burden of comorbidities http://ow.ly/87FQ30m0WM7